2021
DOI: 10.1111/jora.12697
|View full text |Cite
|
Sign up to set email alerts
|

“[E]ven Though We Don’t Have Everything…We Build Our Own Thing”: Exploring Black Girl Space

Abstract: In a racially stratified and oppressive society, Black youth must figure out who they are and what they can achieve while navigating dehumanizing stereotypes that devalue and disregard Black lives. In the current paper, we analyze focus group interviews with Black students at a predominately Black, all‐girls high school to understand the meaning, significance, and potential of Black girl space through an intersectional and developmental lens. Results revealed the challenges and opportunities particularly with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Participants were proud to be a Black girl and described Black girlhood in ways that highlighted their beauty (e.g., natural hair), emphasized their strengths, and celebrated their contributions to the culture. Recent work by Rogers and Butler-Barnes (2022) found that adolescent Black girls' perceptions of their hair were an important part of their identity development, highlighting that hair was a vehicle of empowerment and resistance to Eurocentric beauty standards (Rogers et al, 2021), much like the girls in the present investigation. In our sample, feelings of empowerment were coupled with their desire to overcome barriers associated with their multiple marginalized identities.…”
Section: Black Girls' Identity Development and Meaning Making Of Blac...supporting
confidence: 50%
See 1 more Smart Citation
“…Participants were proud to be a Black girl and described Black girlhood in ways that highlighted their beauty (e.g., natural hair), emphasized their strengths, and celebrated their contributions to the culture. Recent work by Rogers and Butler-Barnes (2022) found that adolescent Black girls' perceptions of their hair were an important part of their identity development, highlighting that hair was a vehicle of empowerment and resistance to Eurocentric beauty standards (Rogers et al, 2021), much like the girls in the present investigation. In our sample, feelings of empowerment were coupled with their desire to overcome barriers associated with their multiple marginalized identities.…”
Section: Black Girls' Identity Development and Meaning Making Of Blac...supporting
confidence: 50%
“…One participant chose to end the interview during the first question and has been excluded from the analysis, resulting in a final sample of 12 adolescent Black girls (Mage = 13.66). Recent studies focused on Black girls' identity development and school experiences have been published with samples of a comparable size (Mims and Williams, 2020;Mayes et al, 2021;Rogers and Butler-Barnes, 2022), which further illustrates that this sample size (n = 12) is effective for examining our research aims. This investigation had an even split in which six of the participants were currently in middle school and six participants were currently in high school.…”
Section: Participantsmentioning
confidence: 81%
“…(2021) demonstrated, hairstyles can be a way of exercising resistance through challenging negative stereotypes and challenging white standards of beauty. In our BLM special issue, Rogers and Butler‐Barnes (2022) articulated how Black girls create counterspaces in active resistance to white supremacy and anti‐Blackness. Likewise, hip hop music and culture can signal a break with norms of whiteness and offer a way to collectively build power in the face of oppression (Anyiwo et al., 2022).…”
Section: Expanding the Conceptualization Of Resistancementioning
confidence: 99%
“…Adolescents are more than the oppressions they face; they resist, have dreams, and have many other rich lived experiences across many developmental contexts. Indeed, many papers in the special series honored the humanity of Black youth and other youth of color by moving beyond a singular focus on the impacts of racism and oppression to documenting the complexity of whole personhood and celebrating strengths (Carey et al, 2022;Carter & Flewellen, 2022;Dunbar, 2022;López Hernández, 2022;Mathews et al, 2022;May et al, 2022;Rogers & Butler-Barnes, 2022). Additionally, anti-racist research can move beyond damage-centered research by conceptualizing research in ways that are action-oriented and community-informed to "engage diverse publics" (Eaton et al, 2021(Eaton et al, , p. 1214.…”
Section: Concep T Ua Lizi Ng R Acism As Syste M Icmentioning
confidence: 99%